2014
DOI: 10.1111/ijd.12688
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the efficacy of diphenylcyclopropenone immunotherapy for the treatment of warts

Abstract: Immunotherapy with DPCP is an effective and well-tolerated option for the treatment of recalcitrant warts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
0
17
1
2
Order By: Relevance
“…This response rate was, however, not achieved until a period around six months later. The mechanism of action involved is best described as an immunomodulatory effect caused by a type IV contact allergic response in the viral lesion .…”
Section: Cutaneous Wartsmentioning
confidence: 99%
See 1 more Smart Citation
“…This response rate was, however, not achieved until a period around six months later. The mechanism of action involved is best described as an immunomodulatory effect caused by a type IV contact allergic response in the viral lesion .…”
Section: Cutaneous Wartsmentioning
confidence: 99%
“…Electrocautery: Electrosurgical ablation with a wire loop is simple to perform and, according to the studies available, on a par with lasers. The average clearance rate stands at 85 %, the rate of recurrence at 14–22 % . However, these studies do not take into consideration that large clusters of condylomata acuminata have to be treated multiple times within 2–3 months, and attempts to treat, for example, an area of 30 cm² with hundreds of condylomata acuminata in a single session (using a laser or electrocautery) are usually unsuccessful and lead to recurrence.…”
Section: Genital Wartsmentioning
confidence: 99%
“…When DPCP immunotherapy is performed for the treatment of warts, variable factors including age, sex, disease duration, location, number and size of warts, and susceptibility to sensitization by DPCP might be associated with the efficacy of treatments. The sensitizing ability, cure rate, and duration of DPCP treatment for warts have been reported in previous studies . However, there has been no study of factors contributing to the duration of treatment with DPCP immunotherapy for periungual warts, which could predict the course of treatment.…”
Section: Introductionmentioning
confidence: 95%
“…Suh et al performed an uncontrolled, open-label study which showed DPCP to have a clearance rate as high as 82.9% [11]. Imiquimod was shown to have a success rate of 44%, ranging from 27% to 89% in an evidencebased review performed by Ahn and Huang [12].…”
Section: Efficacy Of Contact Immunotherapies and Contact Allergensmentioning
confidence: 99%